2004
DOI: 10.1016/j.amjhyper.2004.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Effects of angiotensin II and insulin on ERK1/2 activation in fibroblasts from hypertensive patients*1

Abstract: Angiotensin II stimulated ERK1/2 activation is increased in insulin resistant hypertensive subjects, and it may play a role in the pathogenesis of insulin resistance and accelerated cardiovascular damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 29 publications
1
27
0
Order By: Relevance
“…Fukuda et al [9] showed that endogenous Ang II-stimulated ERK1/2 activation plays a role in the inhibition of insulin signaling in VSMC from spontaneously hypertensive rats. Furthermore, ERK1/2 activity was increased in fibroblasts from hypertensive patients [22] or in the heart tissues from obese Zucker rats with insulin resistance [4]. These findings are consistent with our results shown in Figs.…”
Section: Discussionsupporting
confidence: 94%
“…Fukuda et al [9] showed that endogenous Ang II-stimulated ERK1/2 activation plays a role in the inhibition of insulin signaling in VSMC from spontaneously hypertensive rats. Furthermore, ERK1/2 activity was increased in fibroblasts from hypertensive patients [22] or in the heart tissues from obese Zucker rats with insulin resistance [4]. These findings are consistent with our results shown in Figs.…”
Section: Discussionsupporting
confidence: 94%
“…In human skin fibroblasts from normotensive subjects or hypertensive insulin-sensitive subjects, insulin blunts the Ang II-induced intracellular Ca 2+ mobilization, whereas in the skin fibroblasts of hypertensive patients with insulin resistance, insulin does not modify intracellular Ca 2+ response to Ang II (Ceolotto et al, 2001). Moreover, the ERK1/ 2 phosphorylation evoked by Ang II is significantly higher in skin fibroblasts from hypertensive patients with insulin resistance (Sartori et al, 2004). These results suggest that Ang II-induced signals are enhanced under the insulin resistant status in human skin fibroblasts.…”
Section: Discussionmentioning
confidence: 85%
“…Daily life hyperinsulinemia can result in chronic sympathetic stimulation (Tack et al, 1996) and activate rennin-angiotensin-aldosterone system (RAAS), which plays a key role in balancing blood pressure and electrolyte by synthesizing bioactive factor angiotensin through angiotensin converting enzyme (ACE). Acting through JAK-2/IRS-1/PI3-kinase, JNK and ERK, angiotensin has been shown to inhibit key components of the insulin signaling pathway in insulin-resistant hypertensive subjects (Velloso et al, 1996(Velloso et al, , 2006Sartori et al, 2004). It has been repeatedly reported that angiotensin receptor blockers (ARBs) and angiotensin converting enzyme inhibitors (ACEIs) can improve insulin sensitivity in rodent models of obesity and/or type 2 diabetes associated with insulin resistance (Shiuchi et al, 2004;Henriksen et al, 2001;Park et al, 2006).…”
Section: Introductionmentioning
confidence: 99%